Pembiasaan Disiplin dan Tanggung Jawab melalui Program Makan Bergizi Gratis Sebagai Upaya Penguatan Pendidikan Karakter di Sekolah Dasar - Amal Taqiyuddin; Prana Dwija Iswara; Nurdinah Hanifah (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: Character education, particularly discipline and responsibility, remains a challenge in elementary schools. The Free Nutritious Meal (MBG) Program has the potential to serve as a medium for character habituation through students’ daily activities. This study aimed to describe the habituation of discipline and responsibility among students, examine how the Free Nutritious Meal (MBG) Program supports character education strengthening, and identify its supporting and inhibiting factors. This research employed a qualitative case study approach involving 22 fourth-grade students at SDN 2 Jungjang. Data were collected through participatory observation, in-depth interviews, and documentation and were analyzed qualitatively. The findings revealed that discipline and responsibility were habituated through a series of activities, including handwashing, praying before meals, eating in an orderly manner, maintaining cleanliness, queuing, and organizing eating utensils after use. The MBG Program supported character strengthening through routine habituation, teacher role-modeling, and continuous guidance during program implementation. Supporting factors included teacher role-modeling, clear implementation procedures, and adequate school facilities. Meanwhile, inhibiting factors consisted of limited space, queues at handwashing facilities, and differences in students’ eating pace. In addition, some students reported through self-report that they had begun to apply disciplined and responsible behaviors at home. These findings indicate that the MBG Program can serve as a habituation medium that supports the strengthening of character education in elementary schools.Abstrak: Pendidikan karakter, khususnya disiplin dan tanggung jawab, masih menjadi tantangan di sekolah dasar. Program Makan Bergizi Gratis (MBG) berpotensi menjadi sarana pembiasaan karakter melalui aktivitas keseharian peserta didik. Penelitian ini bertujuan untuk mendeskripsikan pembiasaan disiplin dan tanggung jawab peserta didik, menggambarkan dukungan Program Makan Bergizi Gratis (MBG) terhadap penguatan pendidikan karakter, serta mengidentifikasi faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus pada 22 siswa kelas IV SDN 2 Jungjang. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi, kemudian dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa pembiasaan disiplin dan tanggung jawab dilaksanakan melalui rangkaian kegiatan cuci tangan, berdoa sebelum makan, makan secara tertib, menjaga kebersihan lingkungan, mengantre, serta merapikan peralatan makan setelah digunakan. Program MBG mendukung penguatan karakter melalui pembiasaan yang dilakukan secara rutin, keteladanan guru, dan pendampingan selama kegiatan berlangsung. Faktor pendukung meliputi keteladanan guru, prosedur pelaksanaan yang jelas, serta ketersediaan fasilitas sekolah. Adapun faktor penghambat meliputi keterbatasan ruang, antrean penggunaan wastafel, dan perbedaan kecepatan makan antarsiswa. Selain itu, sebagian siswa dilaporkan melalui self-report mulai menerapkan kebiasaan disiplin dan tanggung jawab di rumah. Temuan ini menunjukkan bahwa Program MBG dapat menjadi sarana pembiasaan yang mendukung penguatan pendidikan karakter di sekolah dasar.